A photo-curable gel electrolyte ink for 3D-printable quasi-solid-state lithium-ion batteries. Issue 45 (10th November 2021) - Gambe, Yoshiyuki; Kobayashi, Hiroaki; Iwase, Kazuyuki; Stauss, Sven; Honma, Itaru
Abstract : We demonstrate gel electrolytes composed of ionic liquids, silica nanoparticles, and UV-resins, that can be 3D-printed and cured by UV-irradiation. The electrolyte maintains its high Li-ion conductivity, enabling quasi-solid-state Li-ion batteries. Abstract : 3D printing technologies have been adapted to enable the fabrication of lithium-ion batteries (LIBs), allowing flexible designs such as micro-scale 3D shapes. Here, we demonstrate 3D-printable gel electrolytes, printed at room temperature. The electrolyte gel solidified by UV irradiation maintains its structural integrity and high lithium-ion conductivity, enabling fully 3D-printed quasi-solid-state LIBs.